ANALYSIS OF RISK FACTORS FOR HYPERTENSION IN BONTO TALLASA VILLAGE, ULUERE DISTRICT, BANTAENG REGENCY - Herdina; Azis, Rahmawati; Amiruddin, Fitriyah (PT. Jurnal Center Indonesia Publisher, 2025)
This study aimed to identify risk factors associated with hypertension in Bonto Tallasa Village, Uluere Subdistrict, Bantaeng Regency, in 2025. The research examined three factors: family history, excessive sodium intake, and stress. A quantitative case–control design was applied to 60 respondents (30 cases and 30 controls) selected through purposive sampling. The results showed that individuals with a family history of hypertension were about 26 times more likely to develop hypertension than those without such a history, indicating a strong and significant association. Excessive sodium intake increased the risk approximately 3.5 times and was statistically significant. Stress was associated with nearly double the risk, but this association was not statistically significant, possibly due to individual differences in coping mechanisms and measurement limitations of subjective stress levels. This suggests that stress may influence hypertension indirectly through behavioral or physiological pathways. In conclusion, family history and excessive sodium intake are significant predictors of hypertension, while stress contributes to an elevated yet statistically nonsignificant risk. Preventive strategies should emphasize sodium reduction, regular blood pressure monitoring, and effective stress management in daily life.